Secondhand smoke Infiltration in multiunit housing: Health effects and nicotine levels - James L. Repace (Indoor Environments)
Introduction: Approximately 46% of U.S. multiunit housing residents with smoke-free home rules, 29 million persons, experience secondhand smoke infiltration in their apartments. Federal health authorities warn that secondhand smoke exposure in multiunit housing is detrimental to the health of children and nonsmoking adults. However, none of the 50 U.S. States bans smoking in privately-owned multiunit housing, and less than 0.1% of the 91,000 U.S. municipalities do. Materials and methods: This study investigates the health problems reported by 162 nonsmoking residents residing in 104 multiunit apartments in 71 municipalities in 19 U.S. States and the District of Columbia, plus 2 Canadian Provinces. Smoke infiltration was confirmed for residents of 103 nonsmoking apartments using self-deployed passive nicotine monitors from 2006 to 2023. Another five subjects reported health problems from marijuana smoke infiltration confirmed by self-administered marijuana surface wipe tests. The secondhand smoke levels in smokers’ units are estimated using mathematical modeling. Results: Nonsmokers complained of eye, nose, throat, and lung irritation, headache, dizziness, nausea, difficulty in breathing, tachycardia, and asthmatic attacks as well as malodors. Many sought medical care and some were hospitalized. Some regarded their apartments as uninhabitable. About 12% resorted to litigation. Nicotine concentrations in subjects’ apartments ranged from 0.001 to 6.60 µg/m3 (geometric mean, 0.028 µg/m3). Modeled PM2.5 levels for a typical smoker’s apartment estimated air pollution levels ranging from “Very Unhealthy” to “Hazardous” levels of the U.S. Air Quality Index. Marijuana surface wipe tests in 5 units showed Tetrahydrocannabinol (THC) ranging from 1.25 µg/m2 to 6.92 µg/m2. Reported health effects were similar to those with tobacco complaints. Conclusions: Secondhand smoke infiltration from smokers’ apartments into nonsmokers’ apartment units in multiunit housing can provoke major morbidity for nonsmoking residents. Nonsmokers’ efforts to eliminate infiltration by sealing of cracks, air cleaning, or increased ventilation proved futile. Building owners and managers need to be educated about protecting nonsmoking residents’ health and welfare from secondhand smoke infiltration. Smoking of tobacco and marijuana products in multiunit housing should be banned.